Human values and biodiversity conservation the survival of wild species - Tisdell, Clement A.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2014)
This pioneering book explores the influence of human values on the willingness of individuals to pay for the conservation of individual wildlife species (and classes of these), to be for or against their survival, and to favour or oppose their harvesting. Clement Tisdell combines original theories, survey results and experimental findings to assess the economic benefit of conserving particular wild species and to suggest strategies for a sustainable future. With a detailed analysis of 25 species, covering the three classes (mammals, birds and reptiles), this book examines how variations in knowledge and social factors can influence individuals' evaluation of species. Moreover, economics and ecology are combined to propose sound policies for wildlife management and to provide estimates of the net economic benefit of conserving particular species. The first work to provide such extensive analysis of human values and conservation, this book is an essential resource for economists, ecologists and all those interested in wildlife management, environment and nature conservation.
pt. I. Background -- pt. II. Values and support for the conservation of individual species as well as sustainable use strategies -- pt. III. Values and support for the conservation of multiple species as well as sustainable use strategies.
Includes index.
Keywords: Biodiversity conservation; Electronic books